Como un talco fugaz : Imágenes y cine en Nicolás Olivari - Bosoer, Sara Amalia (2015)
Este trabajo parte de indagar las relaciones entre literatura y cine como "presencias latentes" (Rancière 2010), para estudiar cómo las imágenes vistas posibilitan una escritura y un modo del montaje, junto con una reformulación de la noción de imagen poética. Se analiza el poema de Nicolás Olivari "Varieté" (1929), asociado al film del mismo nombre.
This paper starts from the relations between literature and cinema as "latent presences" (Rancière 2010), in order to study how the images that we see on screen make writing and some kind of montage possible, as well as a reformulation of the idea of poetic image. We analyze the poem by Nicolás Olivari "Varieté" (1929), in relation to the homonymous film.
Keywords: Imagen; Vanguardia; Cine; Olivari; Borges; Materiales; Interrupción; Montaje; Poesía; Image; Avant garde; Cinema; Olivari; Borges; Materials; Interruption; Mounting; Poetry